2008
DOI: 10.1093/humrep/den129
|View full text |Cite
|
Sign up to set email alerts
|

What next for preimplantation genetic screening (PGS)? Experience with blastocyst biopsy and testing for aneuploidy

Abstract: Blastocysts more commonly have a normal karyotype than cleavage-stage embryos do. Moreover, blastocysts have also made a metabolic transition from catabolism and recycling of the oocyte's reserves and resources, processes that fuel the first 3 days of cleavage. Although not all blastocysts are karyotypically equal, it is still to be determined to what extent a mosaic karyotype might be a normal feature among embryos, both at the cleavage stage and the blastocyst stage--and when looking for karyotypic abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 11 publications
2
75
0
4
Order By: Relevance
“…Contrary to expectation, results from numerous studies did not show that the PGS-FISH was capable of improving live birth rates in patients of advanced maternal age, with recurrent implantation failure or repeated pregnancy loss [35][36][37][38][39][40][41][42][43][44][45][46]. This is because FISH screening does not make it possible to test for all 23 chromosome pairs.…”
Section: Time Lapse Monitoringmentioning
confidence: 82%
“…Contrary to expectation, results from numerous studies did not show that the PGS-FISH was capable of improving live birth rates in patients of advanced maternal age, with recurrent implantation failure or repeated pregnancy loss [35][36][37][38][39][40][41][42][43][44][45][46]. This is because FISH screening does not make it possible to test for all 23 chromosome pairs.…”
Section: Time Lapse Monitoringmentioning
confidence: 82%
“…Ten prospective, randomized, parallel-group, controlled studies evaluating PGS for aneuploidies in IVF/ICSI versus IVF/ICSI met the inclusion criteria [10][11][12][13][14][25][26][27][28][29][30].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…PGS was performed for advanced maternal age defined as ≥35 or ≥37 years [10], 35 to 41 years [26], ≥38 years [30] and ≥35 years [27]. In one study, PGS was performed for failed IVF cycles and recurrent pregnancy loss [25], whereas in other four studies, PGS was indicated in infertile couples without poor prognosis (general IVF population) [10,11,28,29] or for embryo single transfer [11]. The technique of PGS was broadly similar across the included trials.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Overall, the results of these studies did not support a role for PGS in women of advanced maternal age. Two recent studies of younger women undergoing PGS also failed to show a benefit [24,25]. The latter study used trophectoderm biopsy of day 5-6 blastocysts.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinicians have argued of the need for larger RCTs [25,26,[30][31][32]. And yet others have reasoned there is no need to undertake additional RCTs as well-designed studies (cited above) have already demonstrated no benefit of PGS and to undertake additional studies is unethical in light of the findings from some of the studies that performing PGS may, in fact, be harmful [33,34].…”
Section: Introductionmentioning
confidence: 99%